Manipulation of Intestinal Antiviral Innate Immunity and Immune Evasion Strategies of Porcine Epidemic Diarrhea Virus. (3rd November 2019) - Du, Jian; Luo, Junqiu; Yu, Jie; Mao, Xiangbing; Luo, Yuheng; Zheng, Ping; He, Jun; Yu, Bing; Chen, Daiwen
Abstract : Porcine epidemic diarrhea virus (PEDV) infection causes watery diarrhea, dehydration, and high mortality in neonatal pigs, due to its clinical pathogenesis of the intestinal mucosal barrier dysfunction. The host's innate immune system is the first line of defence upon virus invasion of the small intestinal epithelial cells. In turn, the virus has evolved to modulate the host's innate immunity during infection, resulting in pathogen virulence, survival, and the establishment of successful infection. In this review, we gather current knowledge concerning the interplay between PEDV and components of host innate immunity, focusing on the role of cytokines and interferons in intestinal antiviral innate immunity, and the mechanisms underlying the immune evasion strategies of PEDV invasion. Finally, we provide some perspectives on the potential prevention and treatment for PEDV infection.